Parity and body mass index in US women: A prospective 25‐year study. (22nd August 2013) - Abrams, Barbara; Heggeseth, Brianna; Rehkopf, David; Davis, Esa
<x xml:space="preserve">Abstract</x> Objective To investigate long‐term body mass index (BMI) changes associated with childbearing. Design and Methods Adjusted mean BMI changes were estimated by race‐ethnicity, baseline BMI, and parity using longitudinal regression models for 3, 943 young females over 10 and 25 year follow‐up from the ongoing 1979 National Longitudinal Survey of Youth cohort. Results Estimated BMI increases varied by group, ranging from a low of 2.1 BMI units for white, non‐overweight nulliparas over the first 10 years to a high of 10.1 BMI units for black, overweight multiparas over the full 25‐year follow‐up. Impacts of parity were strongest among overweight multiparas and primaparas at 10 years, ranges 1.4‐1.7 and 0.8‐1.3 BMI units, respectively. Among non‐overweight women, parity‐related gain at 10 years varied by number of births among black and white but not Hispanic women. After 25 years, childbearing significantly increased BMI only among overweight multiparous black women. Conclusion Childbearing is associated with permanent weight gain in some women, but the relationship differs by maternal BMI in young adulthood, number of births, race‐ethnicity, and length of follow‐up. Given that overweight black women may be at special risk for accumulation of permanent, long‐term weight after childbearing, effective interventions for this group are particularly needed.